INTRODUCTION TO THE SPECIAL ISSUE: Continued Israeli Occupation Is a Ticking Time Bomb. (December 2022) - Ben-Meir, Alon
This article introduces the World Affairs 2022 special issue which contains ten contributions, including this one, debating the proposal for an Israeli-Palestinian-Jordanian confederation published in this journal earlier this year. In the present article, I continue and expand some of the arguments in the previous proposal. The notion that the time is not ripe to bring an end to the Israeli-Palestinian conflict is misguided and extremely dangerous. When and how a more conducive environment will be created to restart peace negotiations remains elusive. Even a cursory review of the daily encounters between Israelis and Palestinians in the occupied territories and Gaza point to the intensity of hatred, enmity, and utter contempt they feel toward one another, which if continued unabated will be a recipe for an unprecedented violent conflagration. To avert the inevitable, every concerned individual must do everything humanly possible to help in creating new psychological, political, and physical conditions that would facilitate a dialogue and engender a new momentum to start a process of reconciliation before it is too late. This should eventually lead to the establishment of an independent Palestinian state under the umbrella of an Israeli-Palestinian-Jordanian confederation, where all three countries maintain their independence and can grow and prosper together and live in mutual security and peace.